2017
DOI: 10.1016/j.cofs.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of oat: current evidence and molecular mechanisms

Abstract: 18Oat has historically been considered as a valuable crop due to its nutritional attributes. 19 In recent years, oat has attracted growing attention as a healthy food due to its content 20 of various bioactive compounds that can positively impact human health, such as β-21 glucan, avenanthramides, tocols, sterols, phytic acid and avenacosides. These 22 compounds are involved in the reduction of the risk of cardiovascular diseases (CVD), 23 type 2 diabetes mellitus (T2DM), gastrointestinal disorders and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 51 publications
0
92
0
3
Order By: Relevance
“…Dietary fiber, with roughly 60% as insoluble fiber and 40% as soluble fiber [48], also decreases significantly during germination, since the release of gibberellin, a hormone capable of activating the enzyme β-glucanase, promotes β-glucan degradation, among other polysaccharides [17,49], which would explain the decrease in soluble fiber in our sample. Oats also contain other compounds such as phytic acid (5.6-8.7 mg/g; 0.56-0.87%) [9], which has its content decreased by 15%-35% during even a short three-day germination due to activation of phytase activity [50]. Although high doses of phytic acid inhibit the absorption of metals and minerals in humans, it has been observed that, in small doses, it can function as a protective factor in several chronic degenerative diseases [51]; therefore, current research only seeks to reduce the content of this antinutritional compound in various cereals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary fiber, with roughly 60% as insoluble fiber and 40% as soluble fiber [48], also decreases significantly during germination, since the release of gibberellin, a hormone capable of activating the enzyme β-glucanase, promotes β-glucan degradation, among other polysaccharides [17,49], which would explain the decrease in soluble fiber in our sample. Oats also contain other compounds such as phytic acid (5.6-8.7 mg/g; 0.56-0.87%) [9], which has its content decreased by 15%-35% during even a short three-day germination due to activation of phytase activity [50]. Although high doses of phytic acid inhibit the absorption of metals and minerals in humans, it has been observed that, in small doses, it can function as a protective factor in several chronic degenerative diseases [51]; therefore, current research only seeks to reduce the content of this antinutritional compound in various cereals.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, oats have attracted growing attention as a health food, involved in a lower risk of cardiovascular diseases (CVD), type 2 diabetes mellitus (T2DM), gastrointestinal disorders, and cancer [9]. Those properties have been attributed to their content of various bioactive compounds, such as β-glucan, the main component of the soluble fiber in oats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 . Human consumption has been increasing due to an increased awareness of the health benefits associated with the intake of oat products 4,8,9 . In 1998, the FDA recognized, based on available research data, that the consumption of 3 grams of soluble fibre from oats per day was sufficient to significantly decrease the risk of cardiovascular diseases 10 .…”
Section: List Of Tablesmentioning
confidence: 99%
“…Since then, other studies have been conducted to determine the cholesterol-lowering properties of fibres from other cereals such as barley, however, those from oats are more efficient because of their high molecular weights. Today, more people are consuming oats and oat-related products containing brans or extracted fibres 8 . Oat products include bakery products, oatmeal, ready to eat breakfast cereals, flour, bran, and fibres 11 .…”
Section: List Of Tablesmentioning
confidence: 99%